Why we believe : evolution and the human way of being - Fuentes, Agustin (Foundational questions in science., 2019)
A wide-ranging argument by a renowned anthropologist that the capacity to believe is what makes us human Why are so many humans religious? Why do we daydream, imagine, and hope? Philosophers, theologians, social scientists, and historians have offered explanations for centuries, but their accounts often ignore or even avoid human evolution. Evolutionary scientists answer with proposals for why ritual, religion, and faith make sense as adaptations to past challenges or as by-products of our hyper-complex cognitive capacities. But what if the focus on religion is too narrow? Renowned anthropologist Agustín Fuentes argues that the capacity to be religious is actually a small part of a larger and deeper human capacity to believe. Why believe in religion, economies, love? A fascinating intervention into some of the most common misconceptions about human nature, this book employs evolutionary, neurobiological, and anthropological evidence to argue that belief--the ability to commit passionately and wholeheartedly to an idea--is central to the human way of being in the world.